(untitled) (Revista científica Olimpia, 2021)
The practice of sport has always been carried out in person with direct instruction from the coach and the cooperation of his athletes, but since the pandemic caused by COVID-19 in sports, an unexpected reality has been experienced that have led him to work from virtuality, due to all the restriction and distancing measures established by world organizations and governments. This article offers several conceptual and practical tools on the use of ICT, as a proposed solution to the problematic effects generated in the field of sports training, through the use of information and communication technologies, in a new way of living, working and learning in a complex and dire reality that must find timely answers in the context of the confluence between sport, education and the health emergency. The investigation carried out was carried out from the documentary modality, the general procedure was carried out in two stages; the first for the collection of documentary material and the second for the logical organization of said material. This proposal was based on something different to really apply ICT to face problems, give answers and find solutions, in relation to training possibilities.